Post-socialist international migration: The case of China-to-South Korea ethnic labour migration - Anna Myunghee Kim (Institute for the Study of Labor (IZA), 2010)
This paper examines an atypical south-north labour migration that emerged in the postsocialist international migration system: China-to-South Korea ethnic labour migration. In the past two decades, South Korea has experienced an unprecedented increase in the arrival of foreign labour. The majority of the low-skilled migrant workers come from the People's Republic of China. Based on a multivariate analysis of primary survey data on 525 predominantly undocumented Chinese migrants of Korean descent in Seoul, this study reveals the underexplored economic dimension of ethnic migration in Northeast Asia. Empirical findings on this source of migrant labour in South Korea demonstrate that the China-to-South Korea ethnic population movement is an important yet an unknown dimension of the New Economics of International Labour Migration. The study suggests that ethnic migration from a socialist transition economy to a capital-rich economy linked through ancestral connections must be (re)considered in the context of the changing global migration and demographic landscapes, rather than the ethno-nationally romanticised view of the return of diaspora.
Keywords: J6; 330; ethnic labour migration; post-socialist global migration regime; Northeast Asia; new economics of international labour migration; Internationale Arbeitsmobilität; Ethnische Gruppe; Einwanderung; Südkorea; Auswanderung; Übergangswirtschaft; China